Digitising Dictionaries For Advanced Look-Up And Lexical Knowledge Research In Malay. - Lim, Lian Tze; Tan, Ewe Hoe; Tang, Enya Kong (2007)

(untitled)
Electronic dictionaries need not be mere OCR digitised versions of their paper-form counterparts: they can be made more computer-tractable to facilitate more meaningful operations and data exchange. For instance, explicitly annotating different fields in a dictionary entry allows more targeted look-ups, as we will show using Kamus Dewan as an example. Dictionary data can also be reorganised to enable semantic base search. The wordnet lexical database is one such model, for which we created a prototype for the Malay language. As both the proposed annotated Kamus Dewan and Malay WordNet are compiled according to established standards and guidelines, the data can be aligned with similar lexical resources of other languages. This provides a means for mutual sharing, interchange and enrichment of lexical data and knowledge between Malay and other languages.